2019
DOI: 10.1242/dev.166454
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling promotes lung epithelial lineage commitment by curbing Fgf10 and β-catenin signaling

Abstract: Organ growth and tissue homeostasis rely on the proliferation and differentiation of progenitor cell populations. In the developing lung, localized Fgf10 expression maintains distal Sox9-expressing epithelial progenitors and promotes basal cell differentiation in the cartilaginous airways. Mesenchymal Fgf10 expression is induced by Wnt signaling but inhibited by Shh signaling, and epithelial Fgf10 signaling activates β-catenin signaling. The Hippo pathway is a wellconserved signaling cascade that regulates org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
(140 reference statements)
1
42
0
Order By: Relevance
“…Fgfr2 signaling distally around E15.5 is required for the lung to transition from a branching program into an alveolar differentiation program; as we have previously demonstrated that overexpression of Fgf10 starting from E15.5 onwards prevents this transition by inducing distal epithelial Fgfr2 signaling (Volckaert et al, 2013b;Volckaert et al, 2019). Upregulation of Fgfr2 in the proximal epithelium at this stage also coincides with the differentiation of the basal cell lineage (Volckaert et al, 2013b;Balasooriya et al, 2017;Volckaert et al, 2017;Volckaert et al, 2019).…”
Section: Fgfr1 and Fgfr2 Expression During Embryonic Lung Developmentmentioning
confidence: 71%
“…Fgfr2 signaling distally around E15.5 is required for the lung to transition from a branching program into an alveolar differentiation program; as we have previously demonstrated that overexpression of Fgf10 starting from E15.5 onwards prevents this transition by inducing distal epithelial Fgfr2 signaling (Volckaert et al, 2013b;Volckaert et al, 2019). Upregulation of Fgfr2 in the proximal epithelium at this stage also coincides with the differentiation of the basal cell lineage (Volckaert et al, 2013b;Balasooriya et al, 2017;Volckaert et al, 2017;Volckaert et al, 2019).…”
Section: Fgfr1 and Fgfr2 Expression During Embryonic Lung Developmentmentioning
confidence: 71%
“…Among epithelial cells, we discover a shift in epithelial cell population composition in the distal lung, from alveolar epithelial cells towards enrichment in 150 cell populations that typically reside in the airway. We identify the existence of aberrant basaloid Importantly, they express SOX9, a transcription factor critical to distal airway development, repair, also indicated in oncogenesis (19,20). Anatomically, these cells localize to a highly enigmatic region in the IPF lung, at the active edge of the myofibroblast foci.…”
Section: Discussionmentioning
confidence: 86%
“…These cells express markers of epithelial mesenchymal transition (EMT) such as VIM, CDH2, FN1, COL1A1, TNC, and HMGA2 (9, 10, 11 , 12), senescence related genes including CDKN1A, CDKN2A, CCND1, CCND2, MDM2, and GDF15 (13-15) ( Figure 2C, right) and the highest levels of established IPFrelated molecules, such as MMP7 (16), αVβ6 subunits (17) and EPHB2 (18). The cells exhibit 80 high levels and evidence for gene regulation by SOX9 ( Figure 2C upper panel), a transcription factor critical to distal airway development, repair, also indicated in oncogenesis (19,20). Aberrant basaloid cells were not detected in control lungs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian lung is a complex, stereotypically branched organ, whose development is strictly regulated by multiple signaling pathways. They include fibroblast growth factor (FGF) (Lebeche et al, 1999; Ohuchi et al, 2000; Tichelaar et al, 2000; del Moral et al, 2006; Cardoso and Lü, 2006), WNT (Shu et al, 2005a; Yin et al, 2008), bone morphogenetic protein (Weaver et al, 1999; Lu et al, 2001; Shu et al, 2005b), Sonic Hedgehog (Miller et al, 2004; White et al, 2006), epidermal growth factor (EGF) (Kheradmand et al, 2002), retinoic acid (Malpel et al, 2000), and HIPPO (Volckaert et al, 2019) pathways. Tight interplay of these pathways is essential also for lung epithelial homeostasis, regeneration, and repair (Volckaert and De Langhe, 2015; Volckaert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%